Sistem Pengawasan Aktivitas Santri di Pondok Pesantren K.H Ahmad Dahlan Sipirok - Fadlan Taufiqurrohman; Robie Fanreza (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The focus of research in this thesis is the system for monitoring student activities at the K.H Ahmad Dahlan Sipirok Islamic Boarding School. To find out this problem, the research method used by researchers is descriptive qualitative. This method is used to describe the actual monitoring system for student activities at the K.H Ahmad Dahlan Sipirok Islamic Boarding School. This research uses data collection techniques by means of interviews, documentation and observation. This research data validity technique uses extended researcher participation in the field, triangulation, and discussion. This research data analysis technique begins with sorting and focusing the data (data reduction), presenting the data (data display), and drawing conclusions. The results of the research on the student activity monitoring system were carried out to ensure that the students participated in carrying out the planned activity program, as well as the principles adhered to by the Islamic boarding school. Student activities that require a monitoring system include entry and exit from the Islamic boarding school, permission to go home and return to the boarding school, tadarus Al-Qur'an, Tahfidzul Qur'an and Hadith, learning in class, congregational prayers, Tapak Suci activities and Hizbul Wathan. The monitoring system implemented is a continuous or ongoing system. The supervision system is carried out by the leadership giving authority to BP4 or Asatidzah to carry out supervision and report it to the leadership in meetings and will be evaluated every month. This monitoring system cannot be separated from providing rewards and punishment.